ECG disease detection & feature extraction by wavelet transformation - Imam, Saif; Tabassum, Tasbiha; ZarinIrtiza (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.